PRESUPOSISI DAN IMPLIKATUR PADA STAND UP COMEDY INDONESIA - Asri Wijayanti (TRANSFORMATIKA, 2016)
This study discusses presupposition and implikature in Abdur’s Stand-up Comedy Indonesia (SUCI) Session 4 Kompas TV. SUCI uses Indonesian language as the main material of the jokes. The jokes in SUCI come from everyday life of the comics. The jokes in SUCI have some massages. It uses pragmatics analysis approach to answer the questions about (1) presupposition and (2) implicature of SUCI 4. The data are oral forms of Kompas TV’s SUCI 4 shows. The data are obtained by the observation method and by taking notes technique. The data analysis uses pragmatics equal methods. The theories used are the theory of background knowledge, presuppotition, and implicature. The analysis shows that first, Comica’s presupposition about the east of Indonesia are geographycal, society, food, technology, and pulic building condition. Secondly, implicature of Abdur stand up comedy are admit a shortage, found out attention, and critics about government role. Keywords: presupposition, implicature, Indonesian stand up comedy.